Effects of soil physico-chemical parameters on Sclerotium rolfsii suppressiveness - Sen, Krishnendu; Roy, Mithu De; Halder, Suman Kumar; Murmu, Mukul; Pati, Bikasranjan; Islam, Sk Saruk; Barman, Ashis Roy; Ray, Sujit Kumar; Mondal, Keshab Chandra; Dutta, Subrata (Acta Biologica Szegediensis, 2023)
The relationship of soil physico-chemical parameters with disease suppressiveness property of soil is not well understood phenomenon. In this regard, the surveys were conducted on the occurrence of collar rot disease caused by Sclerotium rolfsii in two districts (North 24 Parganas and Nadia) of West Bengal Gangetic new alluvial region of India from February to March, 2016. Soil samples were screened through the disease conduciveness and suppressiveness. The physicochemical properties of soils showed that the clay loam soil dominated in new the alluvial region of West Bengal. It was found that soil suppressiveness against S. rolfsii significantly positively correlated with soil aggregate ratio (AR). PCA explained the closeness of the parameters with soil suppressive index (SI) and aggregate stability (AS). Mostly the exponential relationship has been observed among the selected physico-chemical parameters. From this study we found AR, AS and bulk density were most determining parameters for S. rolfsii soil suppressiveness. Such indicators of soil health would be very beneficial for forecasting potential risks and providing guidance on appropriate farming techniques for specific geographic areas or microclimates. However, further investigation is required to fully comprehend the impact of physical and chemical properties on soil suppressiveness.